2011
DOI: 10.1186/1746-4269-7-32
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicinal and ecological status of plants in Garhwal Himalaya, India

Abstract: BackgroundThe northern part of India harbours a great diversity of medicinal plants due to its distinct geography and ecological marginal conditions. The traditional medical systems of northern India are part of a time tested culture and honored still by people today. These traditional systems have been curing complex disease for more than 3,000 years. With rapidly growing demand for these medicinal plants, most of the plant populations have been depleted, indicating a lack of ecological knowledge among commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
41
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 26 publications
5
41
0
2
Order By: Relevance
“…9,10 In folk medicine of Gharwal region, fruits of this plant are traditionally being used in treatment of digestive disorders. 11 It is well documented that ripen fruits are considered as edible by many tribes while tender leaves and twigs are used as fodder, leaf extract is used as a tonic for hair loss and woods are used as a major fuel source in the central Himalayan region. [12][13][14] The leaves are consumed as tea beverages by the Monpa Community of Tawang, Arunachal Pradesh (India).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In folk medicine of Gharwal region, fruits of this plant are traditionally being used in treatment of digestive disorders. 11 It is well documented that ripen fruits are considered as edible by many tribes while tender leaves and twigs are used as fodder, leaf extract is used as a tonic for hair loss and woods are used as a major fuel source in the central Himalayan region. [12][13][14] The leaves are consumed as tea beverages by the Monpa Community of Tawang, Arunachal Pradesh (India).…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have been carried out on the ethnomedicinal uses of the plants described from the different parts of India [5,11,12]. However, the ecological studies of medicinal plants in the Himalayan region are lacking.In the recent survey, the informants suggested that medicinal plants are an important source for daily healthcare and the associated knowledge is traditionally transmitted, which is also reported in earlier studies and suggested that these species help maintain the ecological balance of the area by decreasing soil erosion and increasing moisture in the soil, thus improving conditions for human and livestock needs [5].Informants are well aware about the knowledge of plants that how they are disappearing due to overexploitation. But not aware of ecological information of the plants which indicate the future performance of the species survival.…”
mentioning
confidence: 99%
“…The people of the Himalayan region are well aware of the traditional use of medicinal plants, but the ecological distribution of the species are unknown, which tell us the presence of species in the nature and further its utilization for sustainable long-term use. Although many studies have been carried out on the ethnomedicinal uses of the plants described from the different parts of India [5,11,12]. However, the ecological studies of medicinal plants in the Himalayan region are lacking.…”
mentioning
confidence: 99%
See 2 more Smart Citations